The Influence of the Family Environment on the Formation of Learning Attitudes in Adolescents - Belgies Anastasya Maulida; Luthfiyyah Zahroh; Moamar Satria Kuswandaru; Riyan Hidayat; Ummi Masrufah Maulidiyah (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
Adolescence is not merely a stage of development, but also a journey toward adulthood, or a bridge between the certainty of childhood and the freedom of adulthood. During this period, the family plays a key role as the primary environment in which identity, motivation, and emotional understanding are formed. This synthesis combines eight empirical studies published between 2022 and 2025 in China, Canada, and Turkey to explore how family closeness, autonomy support, parental expectations, peer relationships, and family structure influence adolescents' motivation, emotional well-being, and academic competence. Findings indicate that adolescents thrive when love is expressed as trust, expectations are balanced with empathy, and autonomy is encouraged rather than controlled. Peer relationships extend the emotional language of the family to the wider social world. Despite differing cultural contexts, universal truths remain: the human need to feel accepted, to grow, and to be understood. This study proposes viewing adolescence as a relationship to be nurtured, not a problem to be solved.